2002
DOI: 10.1097/00005768-200209000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Accumulating brisk walking for fitness, cardiovascular risk, and psychological health

Abstract: These findings suggest that three short bouts (10 min) of brisk walking accumulated throughout the day are at least as effective as one continuous bout of equal total duration in reducing cardiovascular risk and improving aspects of mood in previously sedentary individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
176
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(192 citation statements)
references
References 32 publications
13
176
1
2
Order By: Relevance
“…Because the study sought to examine the physiological effects of the exercise prescription, as opposed to whether the prescription was behaviourally/ecologically valid, the intention-to-treat principle was not employed. Compliance was defined as completing at least 60% of prescribed sessions [7] and, as a result, two subjects were excluded (1 single-bout walker, 1 accumulated-bout walker). Data are therefore presented for 32 subjects (17 women) who completed the study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because the study sought to examine the physiological effects of the exercise prescription, as opposed to whether the prescription was behaviourally/ecologically valid, the intention-to-treat principle was not employed. Compliance was defined as completing at least 60% of prescribed sessions [7] and, as a result, two subjects were excluded (1 single-bout walker, 1 accumulated-bout walker). Data are therefore presented for 32 subjects (17 women) who completed the study.…”
Section: Resultsmentioning
confidence: 99%
“…As the subjects in the present study were normotensive at baseline it was unlikely that significant decreases in BP would occur. In walking studies which have used individuals with BP b129/84 mm Hg, the majority have reported non-significant changes in systolic BP or diastolic BP [7,9,10,13,34,[39][40][41]. Exercise training generally results in BP lowering following exercise which is greater in hypertensive patients than in normotensive subjects [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several pedometer-based interventions have resulted in significant improvements in weight or body mass index (BMI), waist circumference (WC), and other risk factors for diabetes and cardiovascular disease (Gray et al 2009;Pal et al 2009;Freak-Poli et al 2011). Furthermore, the earlier studies demonstrated that even short bouts of brisk walking of 10 minutes (min) accumulated throughout the day are at least as effective as one continuous bout (30 min) of a similar level of activity in improving cardiovascular risk, lipid profiles, fasting plasma insulin and cardiorespiratory fitness (Donnelly et al 2000;Moreau et al 2001;Murphy et al 2002). Consequently, recent guidelines, based on this evidence, recommend that moderate to vigorous physical activity should be performed in bouts lasting 10 min (Haskell et al 2007;World Health Organization 2012).…”
mentioning
confidence: 99%